Abraham Lincoln: A Biography - Charnwood, Lord, (Madison Books, 1998)
No other narrative account of Abraham Lincoln's life has inspired such widespread and lasting acclaim as Charnwood's Abraham Lincoln: A Biography. Written by a native of England and originally published in 1916, the biography is a rare blend of beautiful prose and profound historical insight. Charnwood's study of Lincoln's statesmanship introduced generations of Americans to the life and politics of Lincoln and the author's observations are so comprehensive and well-supported that any serious study of Lincoln must respond to his conclusions.